Art Review + Power 100. (Londen : ArtReview Ltd, 1949)
Founded in 1949, ArtReview is one of the world’s leading international contemporary art magazines, dedicated to expanding contemporary art’s audience and reach, and tracing the ways it interacts with culture in general. Aimed at both a specialist and a general audience, the magazine and its sibling publication, ArtReview Asia (launched in 2013), feature a mixture of criticism, reviews, commentary and analysis alongside commissioned artist projects, guides and special supplements.(https://artreview.com/about/)
Https://artreview.com
Engels
Tijdschriften